AN INTERDISCIPLINARY APPROACH OF ECONOMIC LAW AND HEALTH LAW TO THE HANDLING OF PETTY THEFT OFFENDERS: A LITERATURE STUDY - Sapta Nur Fallah; Iyad Abdallah Al-Shreifeen (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The handling of petty theft cases in Indonesia has been dominated by conventional criminal law approaches that are oriented towards punishment, without considering the multidimensional roots of the problem. This literature study aims to analyse the effectiveness of an interdisciplinary approach that integrates the perspectives of economic law and health law in handling petty theft offenders. The results of the study show that poverty, income distribution inequality, unemployment, and mental health disorders such as chronic stress and kleptomania are the main determinants of petty theft. A treatment model that combines economic intervention through empowerment of marginalised communities and loss value adjustment, as well as mental health intervention through psychological assessment and rehabilitation, has proven to be more effective in reducing recidivism rates and increasing the social reintegration of offenders. Cross-sector collaboration between law enforcement officials, health workers, and social workers in the diversion and restorative justice process also strengthens substantive justice. This research recommends updating regulations and strengthening economic-health policy synergies as strategic steps to create a more inclusive, humane and equitable social protection system in handling petty theft cases.